Roma women activism under communist rule: The cases of the USSR (the 1920s and 1930s) and Bulgaria (1960s and 1970s) - ELENA MARUSHIAKOVA; VESSELIN POPOV (Romani Studies)
This article presents the historical roots of Roma women’s activism, using the example of two countries in different historical periods. The first part is devoted to a discussion on empowering Roma women in the early USSR. It happened in the frames of the general discourse of Soviet national policy in this period and aimed at the complete elimination of the disadvantaged position of women in various spheres (social, economic, political, cultural, educational, etc.). The second part presents the case of socialist Bulgaria, where we have an example of a process of women’s empowerment at the grassroots level. There, we outline the role of the Fatherland Front’s schools for women activists of minority background. In conclusion, we discuss which of the two presented patterns of the development of Roma women’s activism – from top to bottom (as in the USSR in the 1920s and 1930s) or from bottom to top (as in Bulgaria in the 1960s and the 1970s) – proved to be more efficient and gave better results in terms of the socialist women’s emancipation processes and the current position of Roma women in society and their community. This article was published open access under a CC BY licence: https://creativecommons.org/licences/by/4.0.